Effectiveness of personalized granola tailored to the gut microbiota for improving gut environment and mood states - Sasaki, Hiroyuki; Masutomi, Hirofumi; Yamauchi, Yohsuke; Ishihara, Katsuyuki; Fukuda, Shinji (Frontiers in Microbiology, 2025)
The gut microbiota plays a critical role in host metabolism, immunity, and mental health. Short-chain fatty acids (SCFAs), produced through the gut microbial fermentation of dietary fibers, are essential metabolites influencing host physiology. Previous studies have suggested that dietary interventions impact SCFA production, but individual responses vary owing to gut microbiota composition. This study sought to investigate whether personalized granola, formulated based on an individual’s gut microbiota, enhances SCFA production and improves metabolic and mental health outcomes. A single-arm, single-blind, before-and-after study was conducted on 99 participants. Personalized granola (BodyGranola®, Calbee, Inc.) was tailored to the gut microbiota composition of each individual by incorporating three prebiotic ingredients selected from six options. Participants consumed 50 g of granola daily for 8 weeks. Fecal samples were collected at baseline, week 4, and week 8 for gut microbiota and intestinal metabolite analysis via 16S rRNA gene sequencing and gas chromatography–mass spectrometry. Mood and defecation were assessed using the Profile of Mood States Second Edition (POMS2), Athens Insomnia Scale (AIS), and defecation questionnaires. Personalized granola consumption tended to increase SCFAs, including acetic acid and caproic acid. The relative abundance of Bifidobacterium also increased. POMS2 assessments indicated improvements in vitality and total mood disturbance scores. Stool volume increased, but bloating and gas accumulation worsened. Microbiota-type-specific variations in metabolite production were observed. Personalized granola enhances SCFA production and improves mood, suggesting that dietary interventions tailored to gut microbiota composition may optimize health outcomes. Future studies should explore gut microbiota-based precision nutrition in larger, controlled trials.